The Effect of the Third Party Funds on People's Business Credit and Micro Business Segment Profitability - Nanang Saady; Theresia Pradiani; Yunus Handoko (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2020)
This study aims to reveal the direct effect of third-party funds (TPF) on People's Business Credit (PBC), Profitability, and the immediate effect of PBC on profitability, as well as the indirect effect of TPF on profitability through PBC.  The study employs multiple linear regression data analysis through data processing using the Micro Business segment financial statements. The population and sample were the data of monthly TPF, Micro PBC, and profitability in the form of a Return on Assets (ROA) ratio from 2017 to 2019 period. The research target is the Micro Business segment in the Regional Office of PT. Bank Rakyat Indonesia (Persero) Tbk. (BRI) Malang. The results of the data analysis indicate that TPF has a direct effect on the increase of PBC and indirect impact on profitability, as well as an immediate effect of the increase PBC on the decrease of profitability